Achieving Methodological Alignment When Combining QCA and Process tracing in Practice. (January 2018) - Beach, Derek
This article explores the practical challenges one faces when combining qualitative comparative analysis (QCA) and process tracing (PT) in a manner that is consistent with their underlying assumptions about the nature of causal relationships. While PT builds on a mechanism-based understanding of causation, QCA as a comparative method makes claims about counterfactual causal relationships. Given the need to ensure alignment between the ontological understandings of causation that underlie a method and methodological practice, the different ontological foundations result in methodological guidelines that contradict each other, forcing the analyst to choose whether to be more in alignment with one or the other method. This article explores the implications of contrasting guidelines in a practical case study, where a QCA for sufficiency is followed by two PT case studies of positive cases.